The role of fathers and care-giving arrangements in informal settlements in Kenya and Ethiopia - Owino, George Evans; Yigezu, Moges (Frontiers in Public Health, 2023)
Introduction: Quality childcare has been associated with multiple long-term benefits for children including improved school readiness, better educational outcomes and improved health and productivity. Evidence suggests that returns on investment are much higher when targeted at the youngest children, especially during the first 1,000 days. Despite the evidence and potential benefits, investments to make high-quality childcare accessible to the neediest families are not commensurate. Nearly 350 million eligible pre-primary school-age children have no access to quality childcare globally with low-and middle-income countries being especially affected. This study sought to establish the role of fathers and the childcare arrangements in selected urban informal settlements, large agricultural settlements around flower farms and female penal institutions in Kenya and Ethiopia. Methods: A mixed methods design was adopted with quantitative data being collected from 635 mothers of children of 0-3 years from both countries using a structured household questionnaire. The data reported in this article excludes penal institutions from where only qualitative data was collected virtually given that at the time of the study, access was restricted due to Covid-19 related restrictions. Results: Findings show that fathers played a major role in childcare according to 74% of respondents in Kenya and 57.7% in Ethiopia. This involvement is mainly through providing financial support for basic needs for the family and the child and for accessing health care. Fathers who were minimally involved had either left home permanently, had another family, was working far from home or was working long hours. It was revealed that significant proportions of children had been left behind by their mothers without adult supervision. Neighbors and siblings younger than 18 years provided most of the alternative care with daycare centers only accounting for 13.4% of care in Kenya and 6.3% in Ethiopia respectively. Conclusions: The findings revealed that fathers are fairly involved in childcare mainly through providing necessary resources. Parents and guardians in these settlements had access to a mix of care arrangements including unpaid and paid neighbors, toddler's siblings, with limited access to daycare services. It is recommended that governments consider investing in childcare services in informal settlements.